Analysis of Rural Innovation As An Effort To Improve Community Welfare - Adibah Sayyidati (International Journal of Regional Innovation, 2021)
In Government Regulation No. 38 of 2017 concerning Regional Innovation, regional innovation aims to improve the performance of local government administration. In order to achieve the objectives as intended, the target of regional innovation is directed at accelerating the realization of public welfare through improving public services, empowerment and community participation and increasing regional competitiveness. The purpose of this study is to describe and explain how innovation in rural areas is carried out and to analyze the factors and impacts of these innovations for each region with various phenomena. This research uses a qualitative approach. The data collection technique used by researchers is to conduct literature studies related to research in order to obtain relevant concepts. Can create something better, more functional, easier and such. Where, the innovations carried out by the three districts have distinctive characteristics, are new ideas that have never been published before, carried out in a planned manner, and the various innovations carried out have a purpose, namely to improve quality in various phenomena in accordance with regional characteristics.